Educação a Distância, Polos e Avaliação Regulatória: Narrativas de um quebra-cabeça - Santos, Rodrigo Oliveira (2017)
This study, linked to the research line "Training of Educators" of the Postgraduate Program in Education of the Universidade Metodista de São Paulo, aimed to promote a reflection on the evaluation process to which Higher Education Institutions are subject. Presential Support Pole, offer Distance Higher Education in Brazil. The social and economic changes that have taken place over the last decades emphasize the need for such reflection, considering the growth of enrollments in distance education courses and their representativeness in the offer of Higher Education nowadays. Thus, from the legal organization and the current regulatory evaluative process, it became necessary to understand the role of the University as an educational institution, its interaction with technology and the conditions to which the evaluation interprets this confluence on the qualitative character. In this context, the perspective of those who experience this evaluative process, in the position of evaluated, was necessary so that the express was its interpretation on the social and economic importance of such modality. Therefore, the work sought to investigate: What perceptions emerge from the narratives of the professionals who work in the Distance Learning when they reflect on the evaluation processes carried out by INEP / MEC? As a quality, does current evaluative practice accurately understand the complex relationship between the actors involved in the process of knowledge transmission in what structurally refers to a Presential Support Pole and its involvement with the community where it is inserted? From the theoretical point of view, to understand Higher Education and University (CASPER; HUMBOLDT, 2003; DIAS SOBRINHO, 2010; DEMO, 2010; SANTOS, 2011), the role of EAD (Moore, KEARSLEY, 2013; DRON, 2015) As well as the discussions about the interaction of society and education with technology (PINTO, 2005; LÉVY, 1999; GABRIEL, 2015) until reaching the evaluative relations to qualify the offer of courses and programs supported by new means of communication (DIAS SOBRINHO, And the evaluation of the quality of this study. Still, the reflections on the themes that emerge from narratives (CLANDININ; CONNELY, 2005; FREIRE, 2012, 2015) have become key to the opening of new understandings on the proposed theme. The corpus consists of six hermeneutical interviews / conversations that took place between 2015 and 2016. From the hermeneutic-phenomenological analysis emerged from the narratives of the participants' experiences on the evaluation process of the Distance Learning on the Presential Support Pole, reflections on the paths adopted and its impacts on the organization and offer of courses and on institutions in Brazil.